Faith-Based Understanding: A Trialogic Perspective within the Abrahamic Religions - Ab Majeed Ganaie (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In contemporary times, the world is facing many challenges, some of which are perplexed notions about the different ethnic communities. Among the major faith-based ethnicities are Abrahamic religions. These religions are centuries old and have shared a legacy as well. However, despite the fact that their shared legacy should have brought them together and become a source of peace for the rest of the ethnicities, there are many perplexities. Therefore, a process that is a prerequisite to come to the rescue is trialogue. This study attempts to investigate the possibilities and grounds essential for trialogue. This study highlights the origins and fundamental relationships among Abrahamic traditions. It explores the ways and means to understand the perplexities among the traditions. Therefore, this paper uses descriptive and analytical research to examine the need for and importance of a trialogue. The present research finds that on the basis of doctrinal similarity, ethical, and moral obligations understood by the three Abrahamic traditions, there is a clear ground on the basis of which trialogue can be started, and most of the issues and confusions can be erased. This paper has also highlighted some moral duties for a fruitful trialogue process.